If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -4v = 3v Solving 14 + -4v = 3v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-3v' to each side of the equation. 14 + -4v + -3v = 3v + -3v Combine like terms: -4v + -3v = -7v 14 + -7v = 3v + -3v Combine like terms: 3v + -3v = 0 14 + -7v = 0 Add '-14' to each side of the equation. 14 + -14 + -7v = 0 + -14 Combine like terms: 14 + -14 = 0 0 + -7v = 0 + -14 -7v = 0 + -14 Combine like terms: 0 + -14 = -14 -7v = -14 Divide each side by '-7'. v = 2 Simplifying v = 2
| -20=2(x-9) | | (10x^3y)x(2xy^6)= | | ln(x)+ln(2x^2+5)=0 | | f(-6)=6x-6 | | 1568=28lh | | 4x+6-2(2x+3)=3(2x-3) | | -56=8(x-8) | | 5t+1whent=-1 | | 0.5(4-6x)=8x-3(4x+6) | | B-z=b+hx | | 6xy+2y^2-10y=0 | | (7+y)+a=a+7 | | 6(x-2)=-48 | | 7+5y=5a | | 3x-6=4x-15 | | 2x+8=12+6x | | x=(x*0.4)*2.45 | | (7+y)+7=5a | | 4y+2x=9 | | 3x+2x+x=180findx | | F(-9)=6x^2+6 | | 3x^2+4xy-10x-16y=0 | | 5(x+8)=-10 | | y=7-2xand | | 2y+4x=9 | | (m*3)x^2-6*x+(m-2)=0 | | -2(m+1)x+(m-2)= | | 2a+5b+7a= | | (10x^3y)(2xy^6)= | | x=2+0.6666666667y | | x(3x+4y-10)-16y=0 | | kx^2+(1-3k)x+(k-6)=0 |